The studies about the Confederative Cycle and the latin american integration history in the 19th century - Casa Grande, Dirceu Junior [UNESP] (Univ Estadual Londrina, 2018)
The integration efforts of the Latin American nations occurred immediately after the independence processes of the American colonies, known as Latin American Confederative Cycle. Strongly influenced by the European amphictyonies, the Cycle gathered the newly independent nations for the first time at the Panama Congress, in 1826. Despite the integrationist intentions, it failed early in the face of several conflicts between the nations, concerning the local groups' resistance, the United States pressure, among others. This study aims at describe the main aspects and elements that configured the Confederative Cycle and analyzing the studies about the Latin American Integration theme from the singular perspective of the Mexican historian, German Adolfo de la Reza
Keywords: Integration; Independences; Confederative; Amphictyonic; Latin America Palavras